Creative Occupational Therapist: It's About the Client Using Focus Groups to Explore Creativity in Occupational Therapy. (26th April 2018) - Oven, Alenka; Lobe, Bojana
Abstract: Although creativity is an important aspect of occupational therapy theory and practice, there have been few studies that would explore this concept in the context of the occupational therapy process. This was the first qualitative study of creativity in occupational therapy in Slovenia. It was conducted as part of a larger mixed‐methods study and included 22 experienced occupational therapists who participated in four focus groups. The focus of the study was on the exploration of different factors that could contribute to creativity and creative strategies in occupational therapy, in either a positive or a negative way. Since occupational therapy promotes a client‐centered therapy approach, the role of the client as the motivating factor was of particular interest to our study. Six factors that can influence the creativity of occupational therapists emerged from the qualitative analysis (Strauss & Corbin, 1990). While the client was identified as the key factor, the potential of other factors was also recognized. This qualitative study increased the understanding of the concept of creativity and creative behavior in occupational therapy, and also provided empirical material that formed the basis for the development of a questionnaire on creativity in occupational therapy.